KADAR KOLAGEN KULIT DAN TULANG PADA TIKUS BETINA USIA ENAM DAN 12 BULAN YANG DISUPLEMENTASI DENGAN SOMATOTROPIN - Sudatri , Ni Wayan (Jurnal Biologi Udayana; Vol 14 No 1 (2010): Jurnal Biologi, 2010)
The objective of this study is to investigate the effects of somatotropin supplementation on skin and bone collagen concentration of six-month and one-year old female mice. Forty eight female rats were assigned into a randomized block design with 4 factors. The first factor was age with 2 levels (6 months and 12 months). The second factor was somatotropin dosage with 2 levels (0 and 9 mg/kg body weight). The third factor was duration of injection with 2 levels (3 weeks and 6 weeks), and the fourth factor was sampling period with 2 levels (0 and 14 days after somatotropin termination). The results showed that somatotropin supplementation had significant effects on bone (P<0.05) and skin (P<0.01) collagen concentrations.
Keywords: collagen, female rat, somatotropin